PENGARUH SHOPPING LIFESTYLE, STORE ATMOSPHERE, DAN GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA STARBUCKS COFFEE DENPASAR - Ni Putu Melani Gita Sari; I Gusti Ayu Imbayani; I Made Surya Prayoga (VALUES, 2024)
This research was conducted with the aim of finding out the influence of shopping life style, store atmosphere, and greenmarketing on purchasing decisions at Starbucks Coffee Denpasar. The population used in this research is all StarbucksCoffee Denpasar consumers. The number of samples in this study was 75 people who were determined using the PurposiveSampling method. The data in this research was obtained through the results of distributing questionnaires which were lateranalyzed using multiple linear regression analysis techniques. Based on the research results, it can be seen that: Shopping Life Style has a positive and significant effect on Purchasing Decisions. Store Atmosphere has a positive and significant effect on Purchasing Decisions. Green marketing has a positive and significant effect on purchasing decisions at Starbucks Coffee in Denpasar. Looking at the research results, it is recommended that in the future Starbucks Coffee Denpasar canprovide a wider space for its consumers so that they can use it as a place to work or do assignments. With the large area of Starbucks Coffee Denpasar, it can be used for students studying in groups or for workers who want to hold meetings and so on. This will cause an increase in the number of Denpasar Starbucks coffee consumers.